2012
DOI: 10.1177/0956797611435817
|View full text |Cite
|
Sign up to set email alerts
|

Time Flies When You’re Having Approach-Motivated Fun

Abstract: Time flies when you're having fun, but what is it about pleasant experiences that makes time seem to go by faster? In the experiments reported here, we tested the proposal that approach motivation causes perceptual shortening of time during pleasant experiences. Relative to a neutral state or a positive state with low approach motivation (experiment 1), a positive state with high approach motivation shortened perceptions of time. Also, individual differences in approach motivation predicted shorter perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(58 citation statements)
references
References 29 publications
4
51
1
2
Order By: Relevance
“…We likewise found that the effect of red on time perception varied depending on context; however, the mechanism underlying this effect remains unclear. Gable and Poole (2012) found that approach motivation reduced participants' perceived duration. However, there was no clear context information in the study of Shibasaki and Masataka (2014).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We likewise found that the effect of red on time perception varied depending on context; however, the mechanism underlying this effect remains unclear. Gable and Poole (2012) found that approach motivation reduced participants' perceived duration. However, there was no clear context information in the study of Shibasaki and Masataka (2014).…”
Section: Discussionmentioning
confidence: 97%
“…Meier, D'Agostino, Elliot, Maier, and Wilkowski (2012) found that in a relationship context, red evoked approach motivation. Gable and Poole (2012) found that approach motivation reduced perceived duration in pleasant contexts because participants in these states were engaged in pursuing appetitive objects or goals. In daily life, dating and interviewing are commonly regarded as pleasant and unpleasant conditions, respectively.…”
Section: Colour-in-contextmentioning
confidence: 99%
“…From Psychological time perspective, whereas boredom produce a significant increase in duration judgment, flow is a state in which attentional resources are almost fully allocated for non-temporal information processing and as a result duration judgment is minimized (Time flies by when you are having fun; see Zakay, 2012. For more interpretations of this phenomenon see Gable and Poole, 2012, or Sackett et al, 2010). …”
Section: Psychological Timementioning
confidence: 99%
“…Previous studies demonstrate that it is possible to deliberately customise temporal experiences with efforts to influence our own perceived duration, frequency, timing or allocation of time (Flaherty, 2003). It may also be possible to manipulate other people's perceptions of time, for example by encouraging absorption with attractive images (Gable & Poole, 2012) or presenting filler interfaces during periods of wait (Lee, Chen, & Ilie, 2012). Another study evaluated an active progress bar to make better use of waiting time, proposing samples of secondary activities to be performed below a typical progress bar (Hurter, Girouard, Riche, & Plaisant, 2011).…”
Section: Measuring and Manipulating Perceptions Of Timementioning
confidence: 99%